Stakeholders' Perceptions on the Development of a Tshivenda Scientific Language Register for Teaching Agricultural Sciences - Phalandwa, Ocktovia Livhuwani; Ntuli, Thuli Gladys (Universitas Negeri Semarang, 2025)
The South African government seeks to address the dominance of English and Afrikaans as the primary languages of instruction in most schools by promoting the use of indigenous languages as mediums of instruction. This initiative offers a significant opportunity for Black African learners to engage with subjects like Agricultural Sciences in their native languages. However, questions about the readiness and availability of teaching materials and resources in languages such as Tshivenda remain critical. This study planned to categorise the stakeholders perceptions in developing the Tshivenda scientific language register for animal studies. The data for this qualitative interpretative case study were collected through semi-structured interviews with two teachers and six parents, selected using purposive sampling techniques. Findings revealed initial scepticism among stakeholders due to the lack of Agricultural Sciences terminology in Tshivenda. However, with collaborative efforts and a growing positive attitude toward using indigenous languages, significant progress has been made.